2022
DOI: 10.21203/rs.3.rs-1423588/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence Of The Drying Technique’s Impact On The Biomass Quality Of Tetraselmis Subcordiformis (Chlorophyceae)

Abstract: Rapid drying, cost-effective and safe, will increase the viability of using microalgae for several bio-industrial applications. In this study, five different drying techniques of microalgal biomass were investigated. These include freeze-drying, oven drying, air drying, sun drying, and microwave drying. Morphology, metabolite content, FAME profiling, chlorophyll content, total organic carbon, and total nitrogen were analyzed. Results showed that the freeze-drying technique preserves the highest amounts of chlo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Results of statistical analysis showed that the freeze‐dried samples showed significantly higher ( p < 0.05) lipids (18.37 ± 0.20 mg g −1 dw) and total soluble sugars (44.88 ± 0.22 mg g −1 dw) as compared with oven‐dried and shade‐dried samples (Table 1). These results are in agreement with the observation of Aljabri et al [37] that drying techniques impact the biomass quality of Tetraselmis subcordiformis ( Chlorophyceae ) and reported maximum lipid content under the freeze‐drying method. The lipids in microalgae are enriched in PUFAs such as DHA, EPA, ALA, and so on, and free from cholesterol which is favorable in diseases like atherosclerosis, obesity, and blood pressure [38].…”
Section: Discussionmentioning
confidence: 99%
“…Results of statistical analysis showed that the freeze‐dried samples showed significantly higher ( p < 0.05) lipids (18.37 ± 0.20 mg g −1 dw) and total soluble sugars (44.88 ± 0.22 mg g −1 dw) as compared with oven‐dried and shade‐dried samples (Table 1). These results are in agreement with the observation of Aljabri et al [37] that drying techniques impact the biomass quality of Tetraselmis subcordiformis ( Chlorophyceae ) and reported maximum lipid content under the freeze‐drying method. The lipids in microalgae are enriched in PUFAs such as DHA, EPA, ALA, and so on, and free from cholesterol which is favorable in diseases like atherosclerosis, obesity, and blood pressure [38].…”
Section: Discussionmentioning
confidence: 99%